Incorporating the Markov Chain Model in WBSN for Improving Patients Remote Monitoring Systems - Ali R.R.; Mostafa S.A.; Mahdin H.; Mustapha A.; Gunasekaran S.S. (Springer, 2023)
Body sensor networks; Data mining; Data transfer; Data transfer rates; Electric power utilization; Energy efficiency; Markov processes; Medical applications; Medium access control; Remote control; Soft computing; Contention access periods; Efficiency and reliability; Human arm; Markov chain models; Media access control; Real-time environment; Remote monitoring system; Wireless body sensor networks; Remote patient monitoring